Peran Metode Pembelajaran Market Place Activity (MPA) dalam Meningkatkan Hasil Belajar Siswa Mata Pelajaran Fiqih di Kelas VIII MTs Negeri 3 Bekasi - Hanifa, Surya; Nurul Milla, Sri; Devi, Abrista (Jurnal Dirosah Islamiyah, 2024)
Based on the author's observations of class VIII students at MTs Negeri 3 Bekasi, some students still have low learning outcomes in the Fiqh subject. With this data, it is necessary to improve learning methods in Fiqh subjects. The aim of this research is to find out whether there is a significant difference in improving Fiwih learning outcomes after implementing the Market Place Activity (MPA) method. The method used in this research is the Quasi Experimental Test method. The form of this research design is Nonequivalent Control Group Design, namely research to find the influence of the Market Place Activity method on student learning outcomes in Fiqh subjects in class VIII MTs Negeri 3 Bekasi. In this research, the test was given twice, namely: first, students were given an initial test (pre-test) to determine the extent of students' knowledge in both the control and experimental classes. Second, students were given a final test (post-test) using conventional methods in the control class and using the Market Place Activity method in the experimental class. From the test results, it can be concluded that there has been an increase in learning outcomes for Fiqh Subjects in class VIII at MTs Negeri 3 Bekasi, which was taught using conventional methods, with an average score of 22.74, as well as an increase in student learning outcomes for Fiqh Subjects in class VIII at MTs Negeri 3 Bekasi which is taught using the Market Place Activity method can be seen from the average score of 28.1. Meanwhile, in the T test, there was a difference in the learning outcomes of students in the Fiqh subject in class VIII MTs Negeri 3 Bekasi after the Market Place Activity method was applied. It was seen that the significance was 0.000 < 0.05, so it could be concluded that the Market Place Activity method could improve the learning outcomes of class VIII students. MTs Negeri 3 Bekasi.